Disney's The jungle book - Kipling, Rudyard 1865-1936; Walt Disney Company (Great Britian Cemtum books ltd, 2018)
The adventures of Mowgli, a young boy raised by animals in the Indian jungle
2
Keywords: Animals -- Fiction; Jungles -- Fiction; India -- Fiction